A Bibliometric Analysis of Pesantren's Educational Impact: Insights from The Scopus Database (1994–2022) - Gazali, Erfan; Budiana, Agnes Arum (Jurnal Pendidikan Islam, 2023)
Purpose – This study used bibliometric techniques to evaluate pesantren's academic output. It aimed to decipher trends in pesantren study themes, collaborative authorship networks, the most prolific contributors, frequently cited papers, and prominent affiliations publishing pesantren-centric works from 1994 to 2022. Design/methods/approach – Utilizing Scopus as the primary data source with the keyword "pesantren," this study employed a five-stage investigative approach incorporating tools such as Mendeley Desktop, Publish or Perish, and VOSviewer. After rigorous data screening and revision, 154 documents were identified with 'pesantren' as the central theme in their title. Findings – Pesantren research's trajectory is discernible in three distinct phases: 1994–2008 represents the initiation phase, 2009–2017 marks the development phase, and 2018–2022 signifies the expansion phase. This research broadly classifies the themes into micro and macro topics. The micro dimension delves into the internal dynamics of pesantren, encompassing facets like the education system, prevailing values, traditions, roles of Kyai (pesantren leaders) and Santri (pesantren students), and core subject matters. Conversely, the macro dimension evaluates pesantren's responsiveness and role concerning external dynamics, including ecological shifts, democracy, digital and social media integration, technological advancements, political engagement, and challenges like the COVID-19 pandemic. Research implications – The findings, derived from evaluative and relational techniques, hold significance for scholars in Islamic education. They offer insights that can guide future research efforts, allowing scholars to minimize subjectivity and causality biases in discerning the current state of pesantren studies. Institutions can also factor these findings into their strategic planning for Islamic educational research, especially those concentrating on pesantren. Notably, a limitation of this study is its exclusive reliance on the Scopus Core Collection. Future research endeavors can achieve a more comprehensive perspective by incorporating additional databases, such as WoS, ProQuest, and PubMed, for comparative analysis.